Cognitive concomitants of dopamine system stimulation in parkinsonian patients. Issue 9 (September 1987) - Mohr, E; Fabbrini, G; Ruggieri, S; Fedio, P; Chase, T N
Abstract : Verbal, visuospatial and motor functions were studied in eight Parkinsonian patients both during levodopa stimulated and unstimulated state and in eight matched, untreated, healthy controls. Profound changes in patients' motor status were accompanied by relatively selective effects on delayed verbal memory, a function which was also most impaired compared with controls. With dopaminomimetic therapy, tests of delayed verbal memory consistently improved, but did not reach control performance levels. These results could indicate a functional impairment in the mesocortical dopamine system, which can be attenuated, but not entirely corrected, by dopaminomimetic therapy.